In vitro reconstitution of biological oscillators - van der Vlist, Ewan; de Vries, Susan; Kamenz, Julia (Frontiers in Cell and Developmental Biology, 2025)
Oscillations are fundamental to biological timekeeping and organization, yet understanding how their complex temporal dynamics emerge from underlying molecular interactions remains a significant challenge. In vitro reconstitution offers a powerful bottom-up approach to dissect the minimal components, interactions, and parameters required to generate these rhythmic behaviors. Biochemical reconstruction of minimal oscillators outside of their native cellular contexts allows the direct interrogation of the biochemical, biophysical, and systems-level properties that govern oscillatory dynamics and unravel the governing fundamental design principles. In this review, we summarize the theoretical foundations of biological oscillators and outline the major experimental challenges associated with their in vitro reconstitution. We highlight recent advances in the reconstitution of diverse oscillator types, including the cyanobacterial circadian clock, the Min system from Escherichia coli, and synthetic genetic oscillators such as the repressilator. These case studies illustrate how reconstitution efforts have yielded key mechanistic insights and driven technological innovation. We conclude by exploring emerging tools and future directions that promise to overcome current limitations and broaden the applicability of oscillator reconstitution–both to additional biological systems and to a wider range of scientific questions.